DISTRIBUSI IKAN LAUT UNTUK MENINGKATAKAN PEREKONOMIAN PEDAGANG DI PASAR INPRES KOTA PALU - Salima Salima; Maharani Aulia Cisadane; Nadifa Nasyila; Pandu Akbar Wiguna; Abdillah Abdillah; Nuraisyah Nuraisyah; Andi Maman Firmansyah (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
This research focuses on the distribution of sea fish to improve the economy of traders at the Inpres Market. The aim of the research is to determine the distribution of sea fish in the Presidential Market of Palu City using Talcott Parson's theory. This research method uses a qualitative approach with interview and observation data collection techniques. The informants in this research were 3 people, all three were traders. The results show that (1) the application of functional structure in the distribution of marine fish using Talcott Parson's theory. (2) the actors involved in the distribution of marine fish products by traders in the market. (3) distribution of various types of fish from small to large in accordance with the capabilities of the traders. (4) income from marine fish businesses. This shows that marine fish traders.